2022-RA-995-ESGO Independent prognostic significance of substantial lymphovascular space invasion (LVSI) in a consecutive series of primary LVSI-positive endometrial carcinoma (EC). (20th October 2022) - Kommoss, Stefan; Meyer, Charlotte; Grube, Marcel; Praetorius, Teresa; Brucker, Sara Y; Neiss, Felix; Krämer, Bernhard; Walter, Christina Barbara; Kommoss, Friedrich; Staebler, Annette; Gilks, Blake; Singh, Naveena
Abstract : Introduction/Background: LVSI is known to be associated with unfavorable outcome in EC. Recent studies have shown that the extent of LVSI is one of the strongest prognosticators of local as well as distant recurrence after primary therapy. Therefore current risk-assessment algorithms, such as the ESGO-ESTRO-ESP consensus guidelines, require classification of LVSI as 'substantial' versus 'focal or negative' LVSI. It was the aim of this study to investigate the impact of LVSI quantification in a consecutive series of EC in which LVSI was found to be positive after routine pathology assessment. Methodology: EC patients treated at the Tuebingen University Women's Hospital between 2003 and 2016 were identified. Cases in which LVSI had been reported after routine pathology were independently reviewed by three experienced gynecopathologists according to current clinical practice (review of all tumor-containing H&E stained hysterectomy slides). The final LVSI classification was reached by a majority vote of the expert panel. DNA-sequencing for pathogenic POLE mutations and p53/MMR immunohistochemistry was performed on all cases. Results: After chart review of 770 cases, n=95 LVSI-positive cases were available for further research. LVSI was found to be substantial in 50/95(53%) cases. 5-yr disease-specific survival was 42% in cases with substantial LVSI and 74% in LVSI focal/negative cases. No prognostic impact was observed for molecular classification in this highly selected cohort. While established clinicopathological parameters were shown to be of prognostic significance in univariate analyses, LVSI quantification was shown to be the only independent prognosticator after multivariate analyses (HR 2, 24;p=0, 04). Conclusion: Our results support further LVSI quantification in EC found to be LVSI-positive upon routine pathology assessment. Patients with substantial LVSI are at high risk for relapse and fatal outcome. LVSI quantification may help to guide adjuvant treatment and might be of key importance for the development of new personalized EC treatment strategies.